Dolenc approach for clipping of giant C6 and C7 segment aneurysms of the internal carotid artery - Zhang, Hongwei; Liu, Wei; Gu, Yan; Li, Aimin; Zhang, Dong (Frontiers in Surgery, 2023)
Objective: Surgical treatment for giant aneurysms of ICA-ophthalmic segment (C6) and communicating artery segment (C7) was a challenge for neurosurgeons because of their high risks and poor outcomes. To explore the advantages and disadvantages of the Dolenc approach in the treatment of giant C6-C7 segment aneurysms when choosing non-interventional therapy.We retrospectively reviewed the clinical data of 13 cases with giant C6 aneurysms and 4 cases with giant C7 aneurysms treated by Dolenc approach.Results: All of 17 cases of aneurysms were clipped successfully by Dolenc approach, of which 1 case with ipsilateral MCA occlusion underwent extracranial-intracranial artery bypass after the aneurysm clipping. For clinical outcomes, 6 out of 9 cases with preoperative visual impairment improved after surgery, unchanged in 2 cases, deteriorated in 1 case. 1 case had new-onset vision loss, 4 had new-onset oculomotor paralysis, 3 had surgical side cerebral infarction and 2 had diabetes insipidus. DSA or CTA examination within two weeks after operation showed all aneurysms were completely clipped without residual. After a follow-up of 9 to 12 months, 17 patients were evaluated based on GOS and CTA examination. 14 cases had GOS 5 scores, 2 cases had GOS 4 scores, 1 case had GOS 2 scores and no case had death. None of patients had reurrence based on CTA examination. This is a provisional file, not the final typeset article Conclusion: Through Dolenc approach, we could get more operation space, and expose clinoid segment for temporary occlusion. Therefore, Dolenc approach was a safe, effective and frasible treatment for giant C6-C7 aneurysms.